Planet-forming gas seen with new eyes - Garufi, Antonio (Il Colle di Galileo, 2020)
Planets form around newly born stars in protoplanetary disks. These disks are made up of gas and dust and their chemical composition will affect that of planetary atmospheres. Therefore, study of the gas in protoplanetary disks is fundamental toward an understanding of the conditions under which a habitable planet can form. This is a primary aim of the ALMA-DOT survey carried out by the researchers of the Arcetri Astrophysical Observatory.